Isaiah and prophetic traditions in the book of Revelation : visionary antecedents and their development - Fekkes, Jan, 1923- (Journal for the study of the New Testament. Supplement series, 1994)
This work is concerned with the influence of biblical and prophetic traditions on the author of the book of Revelation, and in particular his use of the prophecies of Isaiah. First, John's own prophetic consciousness and expression is compared with previous Israelite-Jewish and early Christian prophetic conventions. This is followed by an evaluation of John's use of the OT in general, including a discussion of methodology for isolating allusions, the question of the validity of the terms quotation and allusion in Revelation, and the presence of thematic patterns in the author's choice of Scrip.